INCOME ANALYSIS OF DODOL AGROINDUSTRY BUSINESS (CASE STUDY: PASAR BENGKEL VILLAGE, PERBAUNGAN DISTRICT, SERDANG BEDAGAI REGENCY, NORTH SUMATRA PROVINCE) - Fuad, Fuad (Universitas Efarina, 2019)
In accordance with this definition, it is permissible to add other ingredients in the manufacture of fruit dodol, such as glutinous rice flour, tapioca flour and coloring agents, as well as preservatives. The ingredients added must comply with not more than the specified rules. The dodol industry in Perbaungan District, especially in Pasar Bengkel village, is the most dominant agro-industry. The dodol agro-industry is not a new business for the local community. This activity has been going on for decades and is well known to many people, both at the local level and in North Sumatra Province and even dodol Pasar Bengkel has found a place as a souvenir which is in great demand by domestic tourists visiting Serdang Bedagei.